Transitions out of and back to employment among older men and women in the UK - David Haardt (University of Essex, Institute for Social and Economic Research (ISER), 2006)
This paper analyses the labour market transitions of older men and women using data from the British Household Panel Survey (BHPS). I find large peaks in exit rates out of employment at ages 60 (women) and 65 (both sexes) which occur in the exact birthday month. This suggests that pension schemes have strong incentive effects. Discrete-time hazard regression analysis shows that benefits and health status are the two most important determinants of retirement, with effects that are larger than found in previous studies for British and US men. When modelling unobserved heterogeneity I find that the share of movers between work and non-work is twice as high among women as among men.
Keywords: 330